Hydrogeological Evaluation Based on Water Quality Parameters and Groundwater Level Conditions in Kolaka and Tangketada Basins, Southeast Sulawesi - Muhammad Abdul Rahman Salim; Dasapta Erwin Irawan; Imam Achmad Sadisun; Bonanza Herlambang Fredomeseliano; Kurniawan (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
This study aims to evaluate the hydrogeological conditions of Pomalaa through analysis of groundwater flow patterns, groundwater level fluctuations, and water quality parameters. The methods used include geological and hydrogeological mapping, groundwater level measurements, and delineation of groundwater basins based on regional topography and lithological data. Water quality analysis was conducted by measuring temperature, Total Dissolved Solids (TDS), electrical conductivity (EC), and pH parameters. The study area consists of five main rock units, with three types of aquifers based on lithological characteristics, namely intergranular and fractured aquifers, low-yield aquifers, and rare aquifers. The results of the study show that groundwater flow patterns follow natural hydraulic gradients, but fluctuate due to environmental changes and mining activities. Several points show significant water quality degradation, with pH, TDS, and EC values exceeding drinking water thresholds. The water quality index shows variations from very good (57), good (49), poor (23), very poor (22), to unfit for drinking (48). The solution offered by this study is the need for mitigation strategies and sustainable water resource management, which is of utmost urgency to maintain ecosystem balance and ensure the availability of clean water for the community and industry in the future.